Performance differences when using 26- and 29-inch-wheel bikes in Swiss National Team cross-country mountain bikers - Steiner, T.; Müller, B.; Maier, T.; Wehrlin, J. P. (Journal of Sports Sciences, 2016)
The purpose of this study was to analyse the effect of bike type - the 26-inch-wheel bike (26" bike) and the 29-inch-wheel bike (29" bike) - on performance in elite mountain bikers. Ten Swiss National Team athletes (seven males, three females) completed six trials with individual start on a simulated cross-country course with 35 min of active recovery between trials (three trials on a 26" bike and three trials on a 29" bike, alternate order, randomised start-bike). The course consisted of two separate sections expected to favour either the 29" bike (section A) or the 26" bike (section B). For each trial performance, power output, cadence and heart rate were recorded and athletes` experiences were documented. Mean overall performance (time: 304 ± 27 s vs. 311 ± 29 s; P < 0.01) and performance in sections A (P < 0.001) and B (P < 0.05) were better when using the 29" bike. No significant differences were observed for power output, cadence or heart rate. Athletes rated the 29" bike as better for performance in general, passing obstacles and traction. The 29" bike supports superior performance for elite mountain bikers, even on sections supposed to favour the 26" bike.